Effect of individualized exercise during maintenance haemodialysis on exercise capacity and health-related quality of life in patients with uraemia. (June 2014) - Wu, Yongyao; He, Qiang; Yin, Xiaohong; He, Qien; Cao, Shengsheng; Ying, Guanghui
Objective: To investigate the effect of individualized exercise on exercise capacity and health-related quality of life (HRQoL) in uraemic patients during maintenance haemodialysis (MHD). Methods: Patients receiving MHD were divided randomly into a test group, who underwent recumbent cycling exercise during dialysis, and a control group, who performed simple stretching exercises. The same dialysis protocol was used for all study participants. At study start and after 12 weeks, exercise capacity was measured using tests of physical ability; HRQoL was measured using the kidney disease quality of life score (KDQOL-SF™). Results: A total of 65 patients were included in the study: 33 in the control group and 32 in the test group. There were no significant differences in patient characteristics between the two groups at baseline. After 12 weeks, there were significant improvements in exercise capacity and in many of the items of the KDQOL-SF™ in the test group compared with the control group. Conclusion: Individualized exercise during MHD significantly improved the exercise capacity and HRQoL for uraemic patients within a short time period, and could therefore be used as a simple, cost-effective therapeutic approach.